Droplet based microfluidics: spectroscopic characterization of levofloxacin and its SERS detection. Issue 33 (7th September 2015) - Hidi, I. J.; Jahn, M.; Weber, K.; Cialla-May, D.; Popp, J.
<x xml:space="preserve">Abstract</x> The determination of the absorption behavior of levofloxacin (levaquin) on the surface of silver nanoparticles and its determination in aqueous solution by droplet based microfluidics combined with surface enhanced Raman spectroscopy.